Comparative assessment of drought resistance of blackberry varieties (Rubus L.) in the Western Forest-Steppe of Ukraine - Телепенько, Ю. Ю. (Scientific Progress & Innovations, 2018)
The article presents the results of laboratory studies of the influence of high temperatures on the physiological state of the leaves of 25 varieties of blackberries in the Western Forest-Steppe of Ukraine. In the laboratory, water-physical properties, such as water retention capacity, moisture deficit and water content of leaf tissues, were studied. In terms of resistance to loss of moisture, the varieties under study are divided into three groups: high-drought-resistant (Black Diamond, Black Pearl, Chief Joseph, Heaven can Wait, Loch Tay, Natches, Orkan, Nasoloda, Chester, Ouachita), medium-drought-resistant (Karaka Black, Adriene, Аsterina, Brzezina, Cacanska Вestrna, Navaho, Tornfree, Sadove chudo, Jumbo, Kiowa, Reuben) and varieties with low resistance (Apache, Black Butte, Black Magic, Triple Crown). Varieties Natches and Apache, and the highest – Black Butte are characterized by a low indicator of water deficit. The highest waterlogging of blackberry leaf tissues was noted in varieties of Loch Tay (58.9 %), Tornfree (59.7 %) and Brzezina (60.8 %). The least hydrated are the fabrics of varieties Navaho and Black Butte (51.4 and 51.7 % respectively).